(untitled) (ASY SYAR’IYYAH: JURNAL ILMU SYARI’AH DAN PERBANKAN ISLAM, 2025)
The experiment with sharia ticketing by the Central Lombok Police during Ramadan 1446 H presents an important phenomenon in the dynamics of sharia-positive law integration in Indonesia. This policy reflects the emergence of religious-based legal innovation at the local level, while also sparking debates about the limits of state authority, the scope for sharia interpretation in public law, and the position of West Nusa Tenggara (NTB) in the national map of legal pluralism. Theoretically, sharia ticketing demonstrates how siyasah sharia is used to legitimize public policy, but it intersects with issues of formal legality, the principle of legal certainty, and harmonization with national laws. This study aims to analyze the implementation of sharia ticketing, identify problems in its policy formulation, and assess the prospects for its integration into the national legal system. The method used is a qualitative, normative-empirical approach through a case study of the Central Lombok Police, with primary data from interviews with officers, religious leaders, and the community, as well as secondary data in the form of regulations and literature on siyasah sharia. The research findings indicate that Sharia ticketing operates as a cultural innovation, but faces a lack of legal basis, procedural ambiguity, and institutional resistance. This study concludes that the integration of Sharia ticketing is only possible through the formulation of norms compatible with national law and recommends strengthening the regulatory framework based on local wisdom while remaining subject to the principles of the rule of law.